Neural correlates of the dual-pathway model for ADHD in adolescents - Shen, Chun; Luo, Qiang; Jia, Tianye; Zhao, Qi; Desrivières, Sylvane; Quinlan, Erin Burke; Banaschewski, Tobias; Millenet, Sabina; Bokde, Arun L. W.; Büchel, Christian; Flor, Herta; Frouin, Vincent; et al. (The American journal of psychiatry, 2020)
Objective:The dual-pathway model has been proposed to explain the heterogeneity in symptoms - of attention deficit hyperactivity disorder (ADHD) by two independent psychological - pathways based on distinct brain circuits. The authors sought to test whether ...